Cryptic diversity within the Anisoneura aluco-group (Lepidoptera: Erebidae) - Zilli, Alberto; de Vos, Rob (Fragmenta entomologica, 2019)
The aluco-group of the Indo-Australian genus Anisoneura is revised with characterisation of its component species and updating of their distribution. Types of all but one nominal taxa of the group are illustrated. The concept of Anisoneura zeuzeroides Guenée, 1852 is restricted to sole populations from Western New Guinea, while Moluccan (including Kei Islands’) populations previously ascribed to this nominal taxon are distinguished as Anisoneura sphingoides C. Felder, 1861 stat. rev. (= Anisoneura depressa Hulstaert, 1924, syn. nov.), and those from Eastern New Guinea are re-evaluated as Anisoneura papuana Hampson, 1913 stat. rev. The unusual circumstances of the scarce divergence in genitalia characters between species looking externally different (either sphingoides or zeuzeroides vs aluco) and vice versa, that is species almost indistinguishable in habitus albeit strongly differentiated in genitalia (either sphingoides or zeuzeroides vs papuana), is stressed. Lectotypes to Anisoneura hypocyana Guenée, 1852 and Anisoneura sphingoides C. Felder, 1861 are designated.